Riau Youth Leader Club: Empowering the Youth of Riau to Implement Community Empowerment Programs: Riau Youth Leader Club: Pemberdayaan Generasi Muda Riau dalam Mengimplementasikan Program Pemberdayaan Masyarakat - Putri Madona; M. Ihsan Zul; Hamid Azwar; Made Rahmawaty; Satria Perdana A; Tobi Arfan; Memen Akbar; Yuliska; Fifitri Ali; M. Suhairi (Universitas Lancang Kuning, 2024)
The data from Badan Pusat Statistik Provinsi Riau in 2020 indicates that Riau Province is poised to benefit from a demographic bonus, with its population predominantly composed of the younger, productive generation. The abundance of young individuals is anticipated to serve as a driving force in enhancing the quality of life for the surrounding communities. The Riau Youth Leader Club (RiyoLC) is an empowerment program aimed at organizing and implementing community empowerment initiatives within Riau. RiyoLC is envisioned as a platform for Riau's youth to exchange ideas, information, and best practices, empowering them to address local challenges and contribute to the advancement of Riau Province. PT Pertamina Hulu Rokan (PT. PHR) has collaborated with Politeknik Caltex Riau to conduct various capacity-building activities, program development support, and implementation assistance for 34 participants from different regencies and cities within PT. PHR WK Rokan's operational area. The program covered topics such as leadership, problem-solving, critical thinking, project management, communication techniques, and presentation skills. As a result, seven community program proposals have been generated, with three of them receiving implementation support from PT PHR